2023
DOI: 10.1186/s12951-023-01921-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles: emerging roles, biomarkers and therapeutic strategies in fibrotic diseases

Abstract: Extracellular vesicles (EVs), a cluster of cell-secreted lipid bilayer nanoscale particles, universally exist in body fluids, as well as cell and tissue culture supernatants. Over the past years, increasing attention have been paid to the important role of EVs as effective intercellular communicators in fibrotic diseases. Notably, EV cargos, including proteins, lipids, nucleic acids, and metabolites, are reported to be disease-specific and can even contribute to fibrosis pathology. Thus, EVs are considered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 184 publications
0
9
0
Order By: Relevance
“…In Mdr2-/-mice, H19 lncRNA in serum exosomes gradually increased with disease progression, indicating that this biomolecule can develop into an RNA biomarker for cholestatic injury and its progression into more severe disease. Moreover, in biliary cholangitis and biliary atresia patients, the serum level of EV-carried H19 was found to correlate with the severity of fibrotic liver injury [ 136 ].…”
Section: Ev-enclosed Non-coding Rnas As Biomarkers For Detection and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Mdr2-/-mice, H19 lncRNA in serum exosomes gradually increased with disease progression, indicating that this biomolecule can develop into an RNA biomarker for cholestatic injury and its progression into more severe disease. Moreover, in biliary cholangitis and biliary atresia patients, the serum level of EV-carried H19 was found to correlate with the severity of fibrotic liver injury [ 136 ].…”
Section: Ev-enclosed Non-coding Rnas As Biomarkers For Detection and ...mentioning
confidence: 99%
“…Regarding lncRNAs, in subjects with biliary cholangitis and biliary atresia, there is a reported correlation between the severity of fibrotic liver injury and the level of EV-carried lncRNA H19 in the serum [ 136 ]. The DNA methyltransferase 1 (DNMT1)-mediated epigenetic silencing of lncRNA H19 is associated with the activation of hepatic stellate cells, which is involved in liver fibrosis [ 147 ].…”
Section: Ev-enclosed Non-coding Rnas As Biomarkers For Detection and ...mentioning
confidence: 99%
“…For example, macrophage derived EVs carrying with lncRNA GAS5 can lead to EC apoptosis, in response to excessive lipoproteins accumulation ( 75 ). Through targeting miR-138-5p/RhoC axis, EVs from macrophages show pro-fibrotic effect by transmitting circUbe3 ( 76 ). Furthermore, activated CD4 + T cells secretes EVs loading miR-142-3p, to contribute to fibrotic remodeling after myocardial infraction, via activation of myofibroblasts ( 77 ).…”
Section: Molecular Mechanisms Of Vascular Fibrosismentioning
confidence: 99%
“…When first separated from ovine red blood cells in the 1970s, sEVs were considered to be plasma membrane-enclosed organelles of uniform size (50 nm) as a group of natural products from maturing reticulocytes [ 2 ]. Mounting evidence revealed that sEVs (e.g., exosomes) are subcellular vehicles with a size range of 30–200 nm, functioning as intercellular communicators and containing a variety of biomolecule cargoes, such as proteins, nucleic acids, and carbohydrates [ 1 , 3 ]. While inheriting main biological characteristics from parental cells, sEVs play an indispensable role in many physiological and pathological conditions, where their surface proteins may represent diagnostic biomarkers in various diseases and can be found in various body fluids (e.g., urine, blood) and tissues [ 4 ].…”
Section: Introductionmentioning
confidence: 99%